Comparative Effectiveness of Hepatic Artery Based Therapies for Unresectable Colorectal Liver Metastases: A Meta-Analysis - Zacharias, Anthony J. (PLoS One, 2015)
BACKGROUND: Patients with unresectable Colorectal Liver Metastases (CRLM) are increasingly being managed using Hepatic Artery Based Therapies (HAT), including Hepatic Arterial Infusion (HAI), Radioembolization (RE), and Transcatheter Arterial Chemoembolization (TACE). Limited data is available on the comparative effectiveness of these options. We hypothesized that outcomes in terms of survival and toxicity were equivalent across the three strategies. METHODS: A meta-analysis was performed using a prospectively registered search strategy at PROSPERO (CRD42013003861) that utilized studies from PubMed (2003–2013). Primary outcome was median overall survival (OS). Secondary outcomes were treatment toxicity, tumor response, and conversion of the tumor to resectable. Additional covariates included prior or concurrent systemic therapy. RESULTS: Of 491 studies screened, 90 were selected for analyses—52 (n = 3,000 patients) HAI, 24 (n = 1,268) RE, 14 (n = 1,038) TACE. The median OS (95% CI) for patients receiving HAT in the first-line were RE 29.4 vs. HAI 21.4 vs. TACE 15.2 months (p = 0.97, 0.69 respectively). For patients failing at least one line of prior systemic therapy, the survival outcomes were TACE 21.3 (20.6–22.4) months vs. HAI 13.2 (12.2–14.2) months vs. RE 10.7 (9.5–12.0). Grade 3–4 toxicity for HAT alone was 40% in the HAI group, 19% in the RE group, and 18% in the TACE groups, which was increased with the addition of systemic chemotherapy. Level 1 evidence was available in 5 studies for HAI, 2 studies for RE and 1 for TACE. CONCLUSION: HAI, RE, and TACE are equally effective in patients with unresectable CRLM with marginal differences in survival.